A Review of Mathematical Process Models for the Electric Arc Furnace Process. Issue 3 (25th October 2020) - Hay, Thomas; Visuri, Ville-Valtteri; Aula, Matti; Echterhof, Thomas
Abstract : The electric arc furnace is the main process unit in scrap‐based steelmaking. Owing to its importance, numerous mathematical models for predicting the course of the electric arc furnace process have been developed. This article reviews mathematical process models proposed in the literature, identifying the most common modeling approaches, and uses mathematical descriptions for the main phenomena. Furthermore, the validation of such models is discussed in detail. Finally, the article identifies gaps in the existing knowledge and provides suggestions for the further development of mathematical process models. Abstract : Mathematical process models for the electric arc furnace process are reviewed and compared with each other as well as other frequently used approaches such as statistical endpoint models and computational fluid dynamics. The different solutions used for problems such as the heat and mass transfer or the determination of scrap melting rates and the models' capabilities are analyzed and evaluated.